Politik Kewarganegaraan Dalam Industri Musik: Konstruksi Citizenship dan Eksklusi Kebijakan Hak Cipta Musik Di Indonesia - Mayrudin, Yeby Ma'asan; Herlina, Herlina (Department of Political Science, Faculty of Social and Political Science, Udayana University, 2025)
This research examines music copyright as partial welfare efforts and royalty polemics in the music industry. The study aims to analyze how music industry actors perceive state existence in music copyright protection as state obligations toward citizen rights. Rogers M. Smith's citizenship theory is employed to construct musicians' citizenship through copyright protection struggles. Using qualitative phenomenological methods with transcendental phenomenology approach, findings reveal musicians view copyright protection as fundamental needs encompassing piracy protection, data system transparency, economic rights guarantee, and creativity appreciation. Musicians actively advocate their rights through organizations, yet face challenges of legal uncertainty evident in royalty dispute cases, and inclusion-exclusion dialectics where reality shows massive copyright violations persist, uneven education, and unfair royalty distribution systems. The research concludes the state is absent in providing adequate facilities, requiring strengthened state role as facilitator to ensure music copyright protection as integral part of citizenship rights.